THE EFFECT OF TRAINING AND COMPENSATION ON JOB PERFORMANCE: ACCESSING THE MODERATING ROLE OF MOTIVATION (A STUDY OF PUBLIC SECTOR OF PAKISTAN) - Adil, Muhammad; Khan, Asad Sarfaraz; Khan, Junaid Ather (International Journal of Psychosocial Rehabilitation, 2020)
Compensation, motivation and training play a vital role improving performance of employees, thus considered as integral part of any organization. The objective of the study is to find the impact of training and compensation on job performance along with moderating role of motivation. Survey-based data was collected from 160 individuals from different public sector organizations of Pakistan. Close ended questionnaires were used for this purpose. The study founded that training and compensation positively affect the job performance whereas moderating effect of motivation is not proved. This paper is believed to be the first to examine the effect of training and compensation on job performance with the help of motivation in public sector of Pakistan.